HDR brachytherapy versus robotic-based and linac-based stereotactic ablative body radiotherapy in the treatment of liver metastases – A dosimetric comparison study of three radioablative techniques - Mateusz Bilski; Katarzyna Korab; Małgorzata Stąpór-Fudzińska; Julia Ponikowska; Agnieszka Brzozowska; Łukasz Sroka; Ewa Wojtyna; Sylwia Sroka; Marta Szlag; Paweł Cisek; Aleksandra Napieralska (Clinical and Translational Radiation Oncology, 2024)
Purpose: The aim of our study was to compare dosimetric aspects of three radioablation modalities – direct high-dose-rate brachytherapy (HDR-BT) and virtually planned stereotactic body radiation therapy performed on CyberKnife (SBRTck) and Elekta Versa HD LINAC (SBRTe) applied in patients with liver metastases. Material and methods: We selected 30 patients with liver metastases, who received liver interstitial HDR-BT and virtually prepared plans for SBRTck and SBRTe. In all the cases, the prescribed dose was a single fraction of 25 Gy. Treatment delivery time, doses delivered to PTV and organs at risk, as well as conformity indices, were calculated and compared. Results: The longest median treatment delivery time was observed in SBRTck in contrast to HDR-BT and SBRTe which were significantly shorter and comparable. HDR-BT plans achieved better coverage of PTV (except for D98%) in contrast to SBRT modalities. Between both SBRT modalities, SBRTck plans resulted in better dose coverage in Dmean, D50%, and D90% values compared to SBRTe without difference in D98%. The SBRTe was the most advantageous considering the PCI and R100%. SBRTck plans achieved the best HI, while R50% value was comparable between SBRTe and SBRTck. The lowest median doses delivered to uninvolved liver volume (V5Gy, V9.1Gy) were achieved with HDR-BT, while the difference between SBRT modalities was insignificant. SBRT plans were better regarding more favourable dose distribution in the duodenum and right kidney, while HDR-BT achieved lower doses in the stomach, heart, great vessels, ribs, skin and spinal cord. There were no significant differences in bowel and biliary tract dose distribution between all selected modalities. Conclusions: HDR-BT resulted in more favourable dose distribution within PTVs and lower doses in organs at risk, which suggests that this treatment modality could be regarded as an alternative to other local ablative therapies in carefully selected patients’ with liver malignancies. Future studies should further address the issue of comparing treatment modalities in different liver locations and clinical scenarios.